Active dispersal of the endo-anecic earthworm Aporrectodea longa (Ude) in an experimental box - Christoph Emmerling; Heiko Strunk (Soil Organisms, 2012)
We investigated the potential of the horizontal dispersal of the endo-anecic earthworm Aporrectodea longa by using an experimental box of 0.7m3. Two treatments, one with and another without vegetation cover (Miscanthus x giganteus) were compared, each with three replicates and ten earthworm individuals for each replicate. Mean horizontal dispersal of A. longa was 7 cm day-1 in a range of 8 cm (± 3) day-1 in the presence of Miscanthus and 6 (± 2) without. We calculated that the horizontal dispersal per year was in the same range (6 to 8 m yr-1) that was within the typical range of several earthworm species from 2.5 to 14 m yr-1. These findings have significant relevance for studies of earthworm population spread and distribution, especially in light of modelling earthworm immigration potential and velocity, triggered for example through regional climate change.